Potret Pengelolaan Masjid Qaryah Kampung Perlis, Pulau Pinang: Modal Sosial Dan Integrasi Manajemen Modern Dalam Pemberdayaan Umat - Muzakir Muzakir (Jurnal Seumubeuet, 2026)
In the contemporary era, mosques function not only as places of worship but also as centers of education, da‘wah, and community empowerment. This study aims to analyze the management model of Masjid Qaryah Kampung Perlis, Penang, Malaysia, focusing on Qur’anic literacy, da‘wah strategies, social capital formation, financial management, and waqf development. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observation, and documentation and were analyzed using the interactive model of Miles, Huberman, and Saldaña, comprising data condensation, data display, and conclusion drawing. The findings reveal that the Celik Al-Qur’an Program is the mosque’s primary initiative, designed according to community needs through gradual learning activities, including Iqra’, halaqah, talaqqi, tadarus, tajwid, and Qur’anic reflection. The program improves Qur’anic reading skills and facilitates the regeneration of Qur’an teachers to ensure the sustainability of da‘wah. Regular learning activities also strengthen social capital by fostering trust, social networks, and Islamic brotherhood, thereby increasing community participation in mosque programs. These achievements are supported by community-based financial management and the development of waqf assets for establishing a learning center and expanding community services. The study concludes that successful mosque management results from integrating Qur’anic education, professional governance, social capital, and sustainable waqf planning.